A novel SW-ESIW slot antenna and its applications in millimeter-wave array design - Qiang, Jingxia; Xu, Feng; Yang, Ling; Liu, Shui; Zhan, Junlin (Frontiers in Physics, 2023)
A novel structure of slot antenna with high gain and compact size for millimeter-wave (mmW) applications is proposed. This is the first attempt to apply slow-wave substrate integrated waveguide (SW-ESIW) to the field of antennas and their arrays. The removal of dielectric substrate improves the radiation gain. At the same time, the slow wave effect, by means of physical separation of electric and magnetic fields, decreases both the lateral and longitudinal dimensions of the antenna. The SW-ESIW slot antenna can achieve miniaturization while retaining the advantages of high gain of ESIW. To further verify the proposed structure, two slot antenna arrays were designed, fabricated and measured. The 1×4-slot array shows a measured -10dB bandwidth of 16% (30.5-35.8GHz) with a measured maximum gain of 11.69dB. The 4×4-slot array achieves a measured -10dB bandwidth of 7.6% from 31.6 to 34.1GHz with a measured peak gain of 18.75dB. In addition, during the operating band, the radiation pattern is stable. The proposed SW-ESIW antenna structure as a trade-off between gain and footprint, can also be flexibly adjusted to adapt to different requirements. These performances ensure that the antenna array based on the proposed structure is a promising candidate for millimeter-wave wireless applications including the fifth-generation mobile communications.